Biology and control of Rhizoctonia solani on rapeseed : A Review - Verma, P.R. (Phytoprotection, 1996)
Rhizoctonia solani AG2-1 is the principal pathogen causing damping-off and seedling and mature plant root rot (brown girdling root rot) in oilseed rape and canola (Brassica napus and B. rapa) in western Canada and the United States; AG4 isolates mainly attack adult plants and cause basai stem rot. Seedling infection by AG2-1 is favoured by cool weather atthe time of planting, whereas warm weather late in the growing season is more conducive for infection of mature plants by AG4 isolates. Survey data show that disease development is favoured by high soil moisture, low levels of nitrogen, phosphorus and potassium and high levels of copper in fine-textured soils. Moderate resistance in condiment mustard (Sinapis alba) and some other species appears to be genetically controlled and should be utilised in breeding programmes. Carboxin and iprodione in mixtures with insecticide gamma-HCH are recommended in Canada as seed treatments to control damping-off and seedling root rot, but do not control brown girdling root rot.